To factor the expression completely:
Step 1: Rewrite 16 as a perfect square.
16 = 4^2
Step 2: Write the expression with the square term in front.
-121x^2 + 16
Step 3: Rewrite -121 as a perfect square multiplied by -1.
-121 = (-11)^2 * -1
Step 4: Rewrite the expression using the perfect square.
-121x^2 + 16 = (-11x)^2 - 4^2
Step 5: Apply the difference of squares formula.
(-11x)^2 - 4^2 = (-11x + 4)(-11x - 4)
Therefore, the expression 16 - 121x^2 factors completely to (-11x + 4)(-11x - 4).
Factor completely.
16, minus, 121, x, squared
16−121x^2
1 answer